Post-conflict monuments in Bosnia and Herzegovina - Čvoro, Uroš, author.
1 online resource
Keywords: "At a time of dramatic struggles over monuments around the world, this book examines monuments that have been erected in post-conflict Bosnia and Herzegovina (BiH) since 1996. Examining the historical precedents for the high rate of monument-building, and its links to ongoing political instability and national animosity, this book identifies the culture of remembrance in BiH as symptomatic of a broader shift: a monumentalisation and privatisation of history. It provides an argument for how to account for the politics of contemporary nation-state formation, control of space, trauma and revisions of history in a region that has been subject to prolonged instability and crisis. This book will be of interest to scholars in contemporary art, museum studies, war and conflict studies, and European studies"--